Description of Soil and the Climatic Conditions of the Experimental Place in Tashkent Region of Blueberry Plant - Qurbonmurodov Akbar Choriyevich (American Journal of Biomedicine and Pharmacy, 2024)
Common blueberry is included among plants that are not so demanding on soil properties. However, sandy soils where water remains in the soil or, on the contrary, quickly absorbs water, are not suitable for blueberries. In addition, blueberries can only grow in an acidic soil pH environment. These and other soil factors should be taken into account when growing blueberries.